Integrated diffractometry: achieved progress and new performance capabilities - Lizunov, V.V.; Zabolotnyy, I.M.; Vasylyk, Ya.V.; Golentus, I.E.; Ushakov, M.V. (Успехи физики металлов, 2019)
This review provides a brief overview and a discussion of dynamical integrated diffractometry and its functional capabilities. It is demonstrated that the combined use of measurements of integrated diffraction parameters on different diffraction conditions allows determining the parameters of several types of microdefects, which are simultaneously present in a single crystal. These parameters are the total integrated intensity of dynamical diffraction, the contribution of its diffuse component, and their dependences on different diffraction conditions. Examples of the use of integrated diffraction parameters for non-destructive express diagnostics of the characteristics of the defects’ structure of single crystals are discussed. Статтю присвячено обговоренню динамічної інтегральної дифрактометрії та її функціональних можливостей. Показано, що комбіноване використання вимірювань інтегральних дифракційних параметрів за різних умов дифракції уможливлює визначення параметрів мікродефектів декількох типів, одночасно присутніх у монокристалі. Обговорюються приклади використання вимірювання повної інтегральної інтенсивності динамічної дифракції, внеску її дифузійної складової та їхніх залежностей від різних умов динамічної дифракції для неруйнівної експресної діагностики характеристик дефектної структури монокристалічних систем. Статья посвящена обсуждению динамической интегральной дифрактометрии и её функциональных возможностей. Показано, что комбинированное использование измерений интегральных дифракционных параметров при различных условиях дифракции позволяет определять параметры микродефектов нескольких типов, одновременно присутствующих в монокристалле. Обсуждаются примеры использования измерения полной интегральной интенсивности динамической дифракции, вклада её диффузной составляющей и их зависимостей от различных условий динамической дифракции для неразрушающей экспрессной диагностики характеристик дефектной структуры монокристаллических систем.